Urgensi Pengaturan Hukum Dan Tanggung Jawab dalam Telesurgery Di Indonesia (RechtJiva, 2025)
The advancement of technology in the healthcare sector, particularly telesurgery, is growing rapidly in Indonesia. Telesurgery is a remote surgical procedure performed with the assistance of robotic systems and wireless networks, enabling surgeons to operate on patients located at a distance. However, this progress has not been accompanied by adequate legal regulations, leading to a legal vacuum in its implementation—especially when malfunctions result in patient death. This research is a normative juridical study that examines various legal rules and principles using secondary data in the form of primary legal documents. Legal materials were collected through literature study, and the method of interpretation used is prescriptive interpretation. This study addresses the absence of legal regulations governing the practice of telesurgery in Indonesia, particularly concerning criminal sanctions and legal liability. The findings show that the regulation of criminal sanctions is essential to provide legal certainty regarding the responsible parties. An ideal regulation should include a definition of telesurgery, qualifications for medical personnel, the rights and obligations of related parties, supervision of medical devices, risk mitigation, and criminal sanctions for medical negligence and product failure.